Multi-objective crashworthiness optimization of square and octagonal bitubal structures including different hole shapes. (June 2019) - Pirmohammad, Sadjad; Esmaeili-Marzdashti, Sobhan
Abstract: This paper investigates the effects of hole shapes and dimensions on crashworthiness performance of the square and octagonal bitubal structures under impact loading. Several holes with three different shapes including rectangle, hexagon and ellipse are considered on the walls of the square and octagonal structures. For these structures, crashworthiness indicators SEA and PCF are numerically obtained using finite element code LS-DYNA. Based on the results, a significant improvement on the crashworthiness capacity is achieved by employing the technique of creating holes on the walls of structures; such that the hexagonal holes created on the square and octagonal bitubal structures improve the crashworthiness capacity by 60% and 42%, respectively in comparison to the corresponding conventional structures. Interestingly, all the holed structures show less PCF compared to those without hole. In the next phase, the hole dimensions are optimized using NSGA-II (non-dominated sorting genetic algorithm) and ANNs (artificial neural networks) methods to find the optimal structures. The SAW (simple additive weight) method is then implemented on the optimal structures, and the square and octagonal structures having the hexagonal holes are finally found as the best and superior energy absorbing devices. The effect of oblique loading on crushing behavior of the holed structures is also considered. According to the results, the holes created on the structure walls improve the crashworthiness capacity of structures under oblique loading, as well. Highlights: Crushing performance of multi-cell structures with different hole shapes was evaluated. Hole dimensions were optimized using artificial neural network and genetic algorithm. The SAW method was used to select the suitable energy absorbers. Optimal square and octagonal structures with hexagonal holes showed the best results.